2010
DOI: 10.1016/j.colsurfa.2010.08.042
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of the influence of pH on phenol sorption in cationic CTAB micellar solutions

Abstract: Interactions between phenol and cationic cetyltrimethylammonium bromide (CTAB) micelles have been investigated by means of nuclear magnetic resonance spectroscopy. The combined use of 1 H and NOESY techniques revealed that phenol has different preferred locations of interaction depending on the pH. At neutral pH (6.70) conditions, phenol molecules are preferentially located in the outer micelle region, at the micelle-water interface, while at more basic pH (9.94), the deprotonated phenol molecules (C 6 H 5 O -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 31 publications
8
32
0
Order By: Relevance
“…The burying of a charged species in CTABr micelles has already been described in the literature. 38,39 It has been reported that phenol, which is located at the micelle surface when protonated, buries itself into CTABr micelles when it is deprotonated, driven by the favourable electrostatic interactions between the negatively charged phenolate ions and the positive charge of the cationic surfactant head group. As far as Receptor 2 is concerned, the PRE experiments show that its location is not markedly affected by complexation with fluor-ide and this can be explained by the fact that its lipophilicity keeps it in the internal core where it was already hosted before the addition of fluoride.…”
Section: Resultsmentioning
confidence: 99%
“…The burying of a charged species in CTABr micelles has already been described in the literature. 38,39 It has been reported that phenol, which is located at the micelle surface when protonated, buries itself into CTABr micelles when it is deprotonated, driven by the favourable electrostatic interactions between the negatively charged phenolate ions and the positive charge of the cationic surfactant head group. As far as Receptor 2 is concerned, the PRE experiments show that its location is not markedly affected by complexation with fluor-ide and this can be explained by the fact that its lipophilicity keeps it in the internal core where it was already hosted before the addition of fluoride.…”
Section: Resultsmentioning
confidence: 99%
“…NMR spectroscopy was often used for revealing the location of the indicators within the micellar pseudophases [20,25,26], together with theoretical approaches applied to the same or similar systems [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic rings are known to introduce differential ring current effects depending upon their proximity and orientation on neighboring protons . The ring current shifts the resonances of the interacting CH 2 ‐chain protons (low‐frequency or high‐frequency) depending upon whether they interact with the center or the edges of the aromatic rings .…”
Section: Resultsmentioning
confidence: 92%
“…Although solubilization of organics including pollutants and pharmaceuticals in micelles is an intensive area of research, details of the loci of internalization and the intermolecular interactions defining them are seldom elucidated . NMR studies along these lines, however, have been reported on the solubilization of substituted benzenes in CTAB, valsartan in SDS and CTAB, and polyaromatics in nonionic dendritic micelles; however, making direct comparisons with our studies is challenging due to the differences in molecular systems. Kreke et al attempted to assign the resonances of CTAB in presence of dichloro benzoates, but the conclusions were tentative, considering the resonance overlap in this region.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation